2017
DOI: 10.3390/ijms18030668
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art on Functional Virgin Olive Oils Enriched with Bioactive Compounds and Their Properties

Abstract: Virgin olive oil, the main fat of the Mediterranean diet, is per se considered as a functional food—as stated by the European Food Safety Authority (EFSA)—due to its content in healthy compounds. The daily intake of endogenous bioactive phenolics from virgin olive oil is variable due to the influence of multiple agronomic and technological factors. Thus, a good strategy to ensure an optimal intake of polyphenols through habitual diet would be to produce enriched virgin olive oil with well-known bioactive polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 105 publications
2
79
0
Order By: Relevance
“…Observational as well as intervention studies have demonstrated that Mediterranean diet is associated with a lower risk of cardiovascular events . Mediterranean diet is rich in fruits and vegetables, has low content of meat and dairy and includes extra virgin olive oil (EVOO) and a small amount of wine .…”
Section: Introductionmentioning
confidence: 99%
“…Observational as well as intervention studies have demonstrated that Mediterranean diet is associated with a lower risk of cardiovascular events . Mediterranean diet is rich in fruits and vegetables, has low content of meat and dairy and includes extra virgin olive oil (EVOO) and a small amount of wine .…”
Section: Introductionmentioning
confidence: 99%
“…Their roles in food safety and preservation have been studied widely, both in vitro and in food matrix experimental trials . Spices and plants can also be added to olive oil, influencing its characteristics and properties . Different oil aromatization processes have been employed in this context; their choice is very important because the extraction method can affect the acceptability, oxidative stability, and the quality parameters of the resulting enriched oil .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Spices and plants can also be added to olive oil, influencing its characteristics and properties. 7,8 Different oil aromatization processes have been employed in this context; their choice is very important because the extraction method can affect the acceptability, oxidative stability, and the quality parameters of the resulting enriched oil. 9,10 The most traditional method is the infusion of natural materials containing antioxidant molecules and flavor compounds (herbs, spices, and fruits), ground, mixed with oil, and left for a defined time.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the shelf‐life of EVOOs is highly correlated with the natural antioxidant content. In particular, among these antioxidants, phenolic substances, α‐tocopherol, and carotene have key roles in prevention of oxidation (Figueiredo‐González, Reboredo‐Rodríguez, González‐Barreiro, Simal‐Gándara, & Valentão, ; Mora‐Ruiz et al, ; Reboredo‐Rodrıguez et al, ). As such, these have been correlated to the storage stability of EVOOs (Baldioli, Servili, Perretti, & Montedoro, ; Fregapane, Gómez‐Rico, Inarejos, & Salvador, ; Papadopoulos & Boskou, ; Rahmani & Saari Csallany, ).…”
Section: Introductionmentioning
confidence: 99%